Are precipitation characteristics and patterns impacting oak trees decline in the Zagros region of western Iran? - Pedram Attarod; Samira Beiranvand; Thomas Grant Pypker; Vilma Bayramzadeh; Jalil Helali; Zahra Mashayekhi; Jafar Fathi; Hamid Soofi Mariv (Caspian Journal of Environmental Sciences, 2023)
The objective was to investigate if changes in annual, monthly, and seasonal precipitation are associated with emergence of declining oak trees in Iran. Daily precipitation data were obtained from 20 synoptic stations distributed over the Zagros area from 1988-2019. Non-parametric Mann-Kendall (MK) test and Sen's Slope estimator (Qmed value) were applied to identify significant trends in the precipitation data. ‘‘De Martonne’’ climate classification (i.e., De Martonne aridity index (IDM) was used for climate classification. Although most stations showed decreasing trends in annual precipitation during the studied period (1988-2019), these trends were statistically significant at only two stations. The mean number of events per year pre- and post- oak decline was not significantly different (68 events before against 71 events after decline). Most of the annual precipitation in the Zagros region falls in winter and spring (80% in total). However, this ratio decreased after the year 2000 by 6% (not significant) compared with before. The difference between the average annual precipitation, before (1988-2000) and after (2000-2019) the emergence of the oak decline phenomenon, were not statistically significant in any of the climate types (semi-arid: 406 mm vs. 378 mm), Mediterranean (530 mm vs. 489 mm), and humid (924 mm vs. 912 mm) as well as in whole Zagros region (537 mm vs. 508 mm). Although our data suggested insignificant trends in precipitation for most stations, future research should investigate if rising temperature in the Zagros area has resulted in higher evaporation and drier soil thereby accelerating the oak tree decline.